ANALISIS PENGARUH UPAH MINIMUM, KEMISKINAN, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN (Studi Kasus di Kabupaten Kawasan Sleingkar Wilis Periode 2010-2019) - Fanshuri, Rizky (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Income distribution disparity is an economic problems faced in any country. Disparity in East Java, based on the Gini index, in the 2011-2019 period is fluctuating, which indicates that income has not been equally distributed. The Gini index of areas in Selingkar Wilis from 2011 to 2019 is also fluctuating, but is still considered low and medium fluctuation. Special attention and stronger efforts are required to overcome the disparity issue, especially on three variables influential on income distribution disparity. The purpose of this study is to analyze the effects of minimum wage, human development index, and poverty on income distribution disparity in Selingkar Wilis region. This quantitative research uses secondary data, analyzed with Klassen typology and panel data regression. The scope of this research is Selingkar Wilis region from 2010 to 2019, focusing on six regencies. This study finds that minimum wage negatively and significantly influences income distribution disparity, that poverty does not significantly affect the disparity, and that human development index positively and significantly impacts the disparity.